Influenza disease burden among potential target risk groups for immunization in South Africa, 2013–2015. Issue 27 (2nd June 2020) - Tempia, Stefano; Walaza, Sibongile; Moyes, Jocelyn; McMorrow, Meredith L.; Cohen, Adam L.; Edoka, Ijeoma; Fraser, Heather; Treurnicht, Florette K.; Hellferscee, Orienka; Wolter, Nicole; von Gottberg, Anne; McAnerney, Johanna M.; et al.
Highlights: Over 45% of individuals at risk of severe influenza in the general population. Over 80% of influenza-associated severe illness among risk groups. Highest rates of influenza-associated severe illness among pregnant women and elderly individuals. Abstract: Background: Data on influenza burden in risk groups for severe influenza are important to guide targeted influenza immunization, especially in resource limited settings. However, this information is limited overall and in particular in low- and middle-income countries. We sought to assess the mean annual national burden of medically and non-medically attended influenza-associated mild, severe-non-fatal and fatal illness among potential target groups for influenza immunization in South Africa during 2013–2015. Methods: We used published mean national annual estimates of mild, severe-non-fatal, and fatal influenza-associated illness in South Africa during 2013–2015 and estimated the number of such illnesses occurring among the following risk groups: (i) children aged 6–59 months; (ii) individuals aged 5–64 years with HIV, and/or pulmonary tuberculosis (PTB), and/or selected underlying medical conditions (UMC); (iii) pregnant women; and (iv) individuals aged ≥65 years. We also estimated the number of individuals among the same risk groups in the population. Results: During 2013–2015, individuals in the selected risk groups accounted for 45.3% (24, 569, 328/54, 086, 144) of the population and 43.5% (4, 614, 763/10, 598, 138), 86.8% (111, 245/128, 173) and 94.5% (10, 903/11, 536) of the mean annual estimated number of influenza-associated mild, severe-non-fatal and fatal illness episodes, respectively. The rates of influenza-associated illness were highest in children aged 6–59 months (23, 983 per 100, 000 population) for mild illness, in pregnant women (930 per 100, 000 population) for severe-non-fatal illness and in individuals aged ≥65 years (138 per 100, 000 population) for fatal illness. Conclusion: Influenza immunization of the selected risk groups has the potential to prevent a substantial number of influenza-associated severe illness. Nonetheless, because of the high number of individuals at risk, South Africa, due to financial resources constrains, may need to further prioritize interventions among risk populations. Cost-burden and cost-effectiveness estimates may assist with further prioritization.